SAT0184 The effect of smoking on response to tumor necrosis factor-alpha inhibitor treatment in ankylosing spondylitis patients: results from the turkbio registry. (12th June 2018) - Yarkan Tuğsal, H.; Can, G.; Çapar, S.; Zengin, B.; Kenar, G.; Akar, S.; Dalkiliç, E.; şenel, S.; Koca, S. S.; Tufan, A.; Yazici, A.; İnanç, N. and Ellidokuz, H. and Akkoç, N. and Önen, F.
Abstract : Background: Although there is good evidence that smoking has a dose-dependent impact on structural damage progression in ankylosing spondylitis (AS) the evidence is poor for its impact on disease activity, physical mobility, life quality and treatment response. Objectives: We aimed to investigate the impact of smoking on disease acitivity, treatment adherence and treatment response in Turkish patients with AS treated with their first tumour necrosis factor-alpha inhibitor (TNFi) therapy in a real-life cohort. Methods: 561 patients fulfilling the modified New York criteria for AS and treated with their first TNFi therapy since 2011 from 8 centers in Turkey were included in the analysis. Treatment response was evaluated as achievement of "BASDAI50" or "ASDAS Clinically important improvement (CII)" at the 3-months' and 6 months' visits. Clinical and demographic parameters were compared between current/never and current/previous smoker groups. Demographic and descriptive data are presented by medians/interquartile ranges (IQRs). Groups were compared by non- parametric tests (x 2, Kruskal Wallis and Mann Whitney tests). Kaplan Meier plots, Cox and logistic regression analyses were calculated for treatment adherence and treatment response. Results: Among 561 AS patients included in the study, 506 (90%) had known smoking status (37% current, 35% never, 17% previous smokers). The median follow-up time was 1.9 years (IQR 0.85–3.5) and disease duration was 3.1 years (0, 6–7, 7). At baseline, current smokers were younger (34, IQR 29–41) compared with never (38, IQR 30–46 p=0.007) and previous smokers (42, IQR 34–49 p<0, 001). Current smokers had male predominance (n=148, 43.9%; n=85, 25.2%); lower erythrocyte sedimentation rate (28 mm/h (13–42); 34 mm/h, (20–49) and higher change in BASMI (40, IQR 10–57.5; 10, IQR 4–30) compared with never smokers (all p<0.005). HLA status, body mass index, CRP, baseline disease indexes (BASDAI, BASFI, BASMI, HAQ, ASDAS) and treatment response was not found to be different between current and never smoker patients in our population (table 1). In multivariate analysis, male (OR:1, 98; 95% CI (1, 39–2, 82), p<0, 01), HLA positive (OR:1, 54; 95%CI (1, 08–2, 18), p=0, 016) and active DMARD user (OR:1, 84; (95%CI 1, 12–3, 01) p=0, 015) patients had better treatment response and treatment adherence ((HR:1, 93; 95% CI (1, 36–2, 73); HR:1, 60; 95% CI (1, 13–2, 27); HR:1, 80; 95% CI (1, 10–2, 95) all p<0, 005) but smoking status were not significant (p>0, 05). Conclusions: In this study of TNFi-treated AS patients in clinical practice, smoking was not found to be associated with disease activity, treatment response and treatment adherence. Disclosure of Interest: None declared